Interaction Between Social Acceptance and Humanistic Green Techno Educational Capability in Supporting Environmentally Friendly Solar Energy Investments in Jember District - Auliq, Muhammad A'an; Sularso, Raden Andi; Safitri, Julia; Isnarno, Endi (PT FORMOSA CENDEKIA GLOBAL, 2023)
The development of a dynamic energy system requires adjustments to energy policies that are in line with and receive strong support from human resources in government and society. One of the most effective and sustainable policies is encouraging investment in environmentally friendly infrastructure, such as renewable energy. The potential of solar energy, which is a renewable energy source, offers a solution to the energy crisis experienced by developing countries. In this research, a new concept is proposed which is known as